GAMBIR SEBAGAI ANTIBAKTERI DALAM FORMULASI OBAT KUMUR - amos, amos (Badan Pengkajian dan Penerapan Teknologi, 2009)
Gambier is the extract of Uncaria gambir Roxb leaves. The use of gambier in mouthwash formulae is one of the efforts of exploring gambier advantages. The existing commercialized mouthwash have quite a high alcohol. The use of a mouthwashes with alcohol contain more than of 25% will increase the risk of generating. mouth and throat cancers up to 50%. The objective of this research using to find the type and bestconcentration of gambier in the mouthwash formula, so that it could be have accepted by consumer. The experiment was in complete random factorial design with two factors andthree levels. The first factor was gambier concentration (1%, 2%, 3%, 4%, and 5%), and the second factor was tud of storage (at weekly until one month). Result showed that gambier with low catechin (25-35%) and tannins (60-65%) had the highest resistance to Streptococcus mutans (up 41.77 %). The antibacterial activity of gambier mouthwash was in the range 20.45 - 43.24%, while the control (Pepsodent Herbal) was 28.25%. The pH of gambier mouthwash was 4.14 - 4.38, while that of the control was 4.66. The viscosity of the mouthwash was 2.75 - 4.75 cP, while the control was 7.25 cP. Both the gambier mouthwash and the control had showed that gambier mouthwash with gambier concentration of 1 % was the most preferred by consumers.